2005
DOI: 10.1002/jat.1096
|View full text |Cite
|
Sign up to set email alerts
|

Advantage of using CBA/N strain mice in a non-radioisotopic modification of the local lymph node assay

Abstract: The murine local lymph node assay (LLNA) is currently recognized as a stand-alone test method for determining the skin sensitizing potential of chemicals. It has been incorporated into the official test guidelines published by some authorities, including the OECD. To avoid the use of radioisotopes, efforts have been made recently to develop non-radioisotopic modifications of the LLNA. A non-radioisotopic modification of the LLNA was developed previously using 5-bromo-2'-deoxyuridine (BrdU) incorporation (non-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Although the principle of the LLNA:BrdU-ELISA method is close to that of the original radio-isotopic LLNA assay, this non-isotopic method appears to be less sensitive, i.e., the non-isotope LLNA tended to yield lower EC 3 values than the standard LLNA (Takeyoshi et al, 2006). In spite of this, the Interagency Coordinating Committee on the Validation of Alternative Methods (ICCVAM) recently approved use of LLNA:BrdU-ELISA to evaluate sensitization potentials of test agents (ICCVAM, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the principle of the LLNA:BrdU-ELISA method is close to that of the original radio-isotopic LLNA assay, this non-isotopic method appears to be less sensitive, i.e., the non-isotope LLNA tended to yield lower EC 3 values than the standard LLNA (Takeyoshi et al, 2006). In spite of this, the Interagency Coordinating Committee on the Validation of Alternative Methods (ICCVAM) recently approved use of LLNA:BrdU-ELISA to evaluate sensitization potentials of test agents (ICCVAM, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The use of this method is difficult in any laboratory because such a radioisotope (RI)-based method requires special facilities and handling procedures. Several authors have conducted investigations into the development of alternative non-RI methods for performing LLNA (Takeyoshi et al, 2001(Takeyoshi et al, , 2005(Takeyoshi et al, , 2006Lee et al, 2002;Suda et al, 2002;Ehling et al, 2005a, b;Idehara et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Flow cytometric analysis and immunohistochemical assays have been developed to count BrdU incorporation into lymph node cells (Boussiquet-Leroux et al, 1995;Lee et al, 2002, Suda et al, 2002. Takeyoshi et al (2001) investigated BrdU incorporation into lymph node cells by using a cell proliferation ELISA kit but their results for a number of allergens suggested an insufficient sensitivity because the increase in lymph node cell counts was not taken into account when calculating SI values (Takeyoshi et al, 2006). Using this method, DNCB yielded positive results IL-2 levels in terms of pg/ml (mean ± SE).…”
Section: Discussionmentioning
confidence: 99%
“…A non-RI LLNA method based on BrdU incorporation instead of 3 H-methyl thymidine has recently been proposed for the purpose of avoiding the use of RI 16 . Although some papers 22 have suggested that the non-RI method appeared to be less sensitive than the standard LLNA, recent work demonstrated that the use of CBA/N mice provides comparable sensitivity to the standard method 23 .…”
Section: Assessment Of Skin Sensitization Of Nanosilicamentioning
confidence: 98%